An investigation on the number of micropyle contained in the ovum of sturgeon in the south coast of Caspian Sea - Halajian, A.; Pourkazemi, M.; Kalbasi, M.R.; Amini, K. (1999)
Determination of the number of ovum micropyle in three sturgeon species had been the main goal of this research. The study was conducted on 44 specimens of female Persian sturgeon (Acipenser Persicus), 13 specimens of female Stellate sturgeon (A.stellatus) and 8 specimens of female beluga (Huso huso). 50 ova were randomly collected and evaluated from each specimen and totally the micropyles of 3250 ova from three sturgeon species were studied. From the 44 specimens of Persian sturgeon, 13 belonging to the South-East area of Caspian Sea; Golestan province, Shahid Marjani center and 31 of them from the South-West area of Caspian Sea; Guilan province, Shahid Beheshti center; including 21 specimens from the sea and 10 ones from Sefid-rud River. The entire stellate sturgeon specimens and beluga specimens were collected from Guilan province and Golestan province respectively. Based on achieved from results, the average number of micropyls of Persian sturgeon, inhabitant of the eastern part of Caspian sea, was 7.7±1.59 for the western part was 8.7±1.75 and for Persian sturgeon catched from Sefid-rud was 8.3 ± 1.6 in each ovum. Based on evaluation and statistic comparison, no significant difference (P>0.95) was observed between Persian sturgeon of the East and West part, in terms of micropyle number. The average number of micropyle of stellate sturgeon was 4.7±1.51 and for beluga was 5.19±1.59 in each ovum. The average diameters of outer membrane micropyle of ovum in A.Persicus, A.Stellaus and Huso huso were 21.97±1.05 micron, 21.5±1.2 micron and 22.1±0.7 micron respectively; and the average diameters of inner membrane micropyle of ovum were 18.82±1.1 micron, 17.4±1.6 micron and 18.6±1.7 micron respectively.